2020
DOI: 10.1093/europace/euaa264
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of cardiac resynchronization therapy and an introduction to conduction system pacing: a conceptual review

Abstract: In chronic systolic heart failure and conduction system disease, cardiac resynchronization therapy (CRT) is the only known non-pharmacologic heart failure therapy that improves cardiac function, functional capacity, and survival while decreasing cardiac workload and hospitalization rates. While conventional bi-ventricular pacing has been shown to benefit patients with heart failure and conduction system disease, there are limitations to its therapeutic success, resulting in widely variable clinical response. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 72 publications
0
36
0
8
Order By: Relevance
“…Previous studies with epicardial activation mapping indicated that electrical dyssynchrony remained despite the use of BVP, suggesting that activation time and pattern could not be corrected to a physiological level by BVP delivered CRT ( 21 ). Among new strategies of conduction system pacing, although LBBAP could not achieve normal physiological activation maintained via the right bundle as HBP ( 22 , 23 ), compared with BVP, LBBAP is associated with a significantly further decreased QRSd of −29.2 ms, as evidenced in our meta-analysis. In this meta-analysis, greater improvement of LVEF was achieved by LBBAP delivered CRT compared with BVP delivered CRT, which is paralleled with the more remarkable shortened QRSd in patients after LBBAP delivered CRT.…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies with epicardial activation mapping indicated that electrical dyssynchrony remained despite the use of BVP, suggesting that activation time and pattern could not be corrected to a physiological level by BVP delivered CRT ( 21 ). Among new strategies of conduction system pacing, although LBBAP could not achieve normal physiological activation maintained via the right bundle as HBP ( 22 , 23 ), compared with BVP, LBBAP is associated with a significantly further decreased QRSd of −29.2 ms, as evidenced in our meta-analysis. In this meta-analysis, greater improvement of LVEF was achieved by LBBAP delivered CRT compared with BVP delivered CRT, which is paralleled with the more remarkable shortened QRSd in patients after LBBAP delivered CRT.…”
Section: Discussionmentioning
confidence: 58%
“…CRT by biventricular pacing is the only heart failure therapy that improves cardiac function, functional capacity and survival while decreasing hospitalizations 14 . Nevertheless, the response to BiV pacing is variable, ranging from complete normalization of cardiac function to lack of benefit.…”
Section: Discussionmentioning
confidence: 99%
“…We know that CRT is the only known non-pharmacologic HF therapy that improves cardiac function, functional capacity, and survival while decreasing cardiac workload and hospitalization rates in chronic systolic HF and conduction system disease. 6 , 7 However, CRT is not without its limitations. One major limitation of BiV pacing in CRT is the failure of LV lead deployment due to limitations in CS anatomy, 8 and the standard of care suggests epicardial LV lead insertion as the next alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, CSP serves as an attractive bailout strategy in patients with a lack of coronary venous access, diaphragmatic pacing, and/or failure to respond to classic CRT. 7 The 2021 European Society of Cardiology guidelines 11 recommend HBP as a treatment option together with other techniques such as surgical epicardial lead (class IIa level of evidence B indication) in CRT candidates in whom CS lead implantation is unsuccessful.…”
Section: Discussionmentioning
confidence: 99%